4-Methylphenyl 4-chlorobenzoate - Gowda, B. Thimme (International Union of Crystallography, 2007)
The crystal structure of the title compound, C(14)H(11)ClO(2), is similar to those of phenyl benzoate, 4-methylphenyl benzoate and 4-methylphenyl 4-methylbenzoate. The dihedral angle between the phenyl and benzene rings is 51.86 (4)°. The molecules crystallize in planes parallel to ([Image: see text]02).